Promoting Universal Social Policy in MICs - Martínez Franzoni, Juliana (2020)
Reducing poverty levels, improving the distribution of income and improving people’s capabilities are three key challenges of economic development. Many middle-income countries (MICs) have the state capacity and the resources needed to confront these challenges—as evident in Hoy and Sumner’s discussion in chapter 7. Yet they have generally failed to meet these goals, failing to successfully provide healthcare, education, and income support to significant segments of the population. How can this problem be resolved? How should social benefits be provided in the MICs? Should services and transfers be for everyone or focus exclusively on the poor? This chapter provides answers to these questions. Following our previous work and that of others, we argue that to be effective and successful, social policies should be universal, providing the whole population with similar, generous transfers and services (Martínez Franzoni and Sánchez-Ancochea, 2014a; Mkandawire, 2006a; Pribble, 2013). Yet delivering universal social policies in a development context is easier said than done. We propose to take a step back and distinguish between what we want to achieve and how to achieve it. This requires separating the desired policy outputs (coverage, generosity, and equity of benefits) from the specific ways to secure them. To study the latter, we discuss the concept of the policy architecture: the combination of instruments that define what specific benefits are being offered, to whom, and how. Choosing the desirable/feasible policy architecture—one that initially focuses on the poor or one that departs from other groups of the population as well—is both a technical and a political decision. When designing new architectures or reforming existing ones, policymakers must consider the incentives and constraints created in the long run. They should also be aware of the interactions between public and private arrangements and, more specifically, how the latter shapes the former.